Virtual voltage control to redistribute reactive power of generators in a microgrid - Viloria, Eder Alexander Molina; Becerra, John E. Candelo; Durán, Dario Enrique Soto (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The paper examines a strategy for managing voltage control in a microgrid by redistributing reactive power among its distributed generators. Unlike traditional droop control, the new control approach can provide a more accurate reactive power response based on a virtual impedance that helps calculate a virtual voltage. In addition, this virtual impedance is employed for the current controller inverter to improve the results. The adaptive virtual voltage control works well to provide active and reactive power. The proposed control works effectively by balancing the active and reactive power of the grid and maintains the fundamental frequency. The control technique assists the new microgrid (MG) in adapting the operation effectively and redistributing the active and reactive power.